Jómsvíkinga Sǫgur and Jómsvíkinga Drápur: texts, contexts and intertexts - Jesch, Judith (Isländska sällskapet, Uppsala, Sweden, 2014)
Using theories of intertextuality the paper explores the implications of the complex transmission of Jómsvíkinga saga, with its multiple manuscripts, versions and cross-references in other texts. It then concentrates on the story-complex about the Jómsvíkings and the battle of Hjǫrungavágr, rather than the first part of the saga with its focus on Danish kings. The paper explores how this story-complex was realized in skaldic poetry, ostensibly a major source for the prose accounts. Following a survey of all the relevant poetry, the four drápur which treat the Jómsvíkings are analysed in detail. Two of these are roughly contemporary with the events, while two are retrospective, narrative accounts, and there is some evidence of influence from the earlier poems to the later ones. Overall, the analysis shows how the story of the battle of Hjǫrungavágr was narrated in both verse and prose, and reveals the complex intertextual relationships between these narratives.